Prevalence of thyroid disorder among people living with HIV/AIDS (PLHA) on antiretroviral treatment visiting national public health laboratory, Teku, Kathmandu. - Pokhrel, Sujata (2015)
ABSTRACT: Thyroid disorder is common on HIV/AIDS infected patients and its estimation may be useful for the characterization of the different stages of the infection and that may be important for the better management of the HIV infected patients. The objective of this study was to determine prevalence of thyroid disorder and their association with Age, gender, CD4 cell count, duration and types of antiretroviral therapy and stages of infection among HIV infected individuals. This study was carried out in National public Health Laboratory from April 2014 to October 2014. During the study period total 100 samples were screened for the CD4 cell count using flowcytometer, thyroid hormone levels by chemiluminiscence assay method, serum C reactive protein and rheumatoid factor from Kit methods and viral load was determined among only 38 patients with therapy by using real time PCR in virology lab of NPHL. Out of 100 patients, 27% had thyroid disorder with which highest prevalence 8.75% of the subclinical hypothyroidism was found among ART patients while among naïve patients euthyroid sick syndrome was found to be higher i.e. 15% Subclinical hypothyroidism was common among patients with CD4 count between 201-350 call/mm3, were receiving drugs in combination with Zidovudine, Lamivudine and Nevirapin since 4-6 yrs of the duration. Most of them were in second and third stage of the infection. Euthyroid sick syndrome was found mostly among 3rd and 4th stages of the infection having CD4 less than 200cells/mm3. No case of Rheumatoid arthritis was reported but CRP was found to be raise in the patients with euthyroid. Among two cases of the autoimmune thyroiditis one of them had detectable level of CRP suggesting the condition of the Subacute thyroiditis rather than the Graves disease. This study showed high prevalence of subclinical hypothyroidism in HIV infected patients hence regular monitoring of thyroid disorder should be carried out to reduce complicatiuon. Key words: Euthyroid, subclinical hypothyroidism, Subacute thyroiditis, Graves diseases